Flip-Chip Integration of Power HEMTs: A Step Towards a GaN MMIC Technology - Seemann, Kay; Ramberger, Suitbert; Tessmann, Axel; Quay, Rüdiger; Schneider, Joachim; Rießle, Markus; Walcher, Herbert; Kuri, Michael; Kiefer, Rudolf; Schlechtweg, Michael (33rd European Microwave Conference, 2003)
In this paper, flip-chip integration is demonstrated as a method for faster progress towards a GaN MMIC technology by separating the development of active devices and passive matching circuits. This approach offers distinct advantages in the verification of passive components realized on a 2" SiC substrate. A proven 0.3μm GaAs PHEMT technology was used for the transistors that allowed to reproducibly verify both, the flip-chip transitions and the behaviour of the coplanar SiC structures. As an example, three X-band amplifiers in flip-chip technology are presented that demonstrate the feasibility of the technology. © 2003 EUMA.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LETE.flipch
Keywords: Gallium arsenide; Gallium nitride; Gold; HEMTs; Integrated circuit technology; MIM capacitors; MMICs; MODFETs; Silicon carbide; Substrates